Parental perspectives on Danish full-day schools for ethnic-minority students - Holm, Lars (International Journal about Parents in Education, 2023)
With regard to ethnic-minority students, different education-policy strategies have been discussed and tested in Denmark over the past 30 to 40 years. The most recent are the so-called “full-day schools”, which have been established in a number of municipalities that have areas with a high concentration of ethnic-minority students. Based on an understanding of full-day schools as an education-policy strategy, I use a policy-ethnographic perspective to analyse a trial that took place in the three local schools in the area of Vollsmose in Odense, Denmark. One class from each school was selected for the three-year research project. Using qualitative data from the research project I describe and analyse parents’ reactions to and interpretations of the full-day school trial. These insights illuminate not only the different attitudes of an often overlooked group of actors in response to a trial at their local schools, but also the contradicting values and norms that apply to schooling ethnic-minority students on a more general level. The findings suggest a need for a highly differentiated and “non-ethnicised” view of ethnic minority parents.